Mengidentifikasi Jenis Sampah Rumah Tangga dan Penanggulangannya di Kelurahan Saoka Kota Sorong Provinsi Papua Barat - Melisa Ch Masengi; Melani Manurung; Magdalena Taa (INTEGRATED OF FISHERIES SCIENCE, 2022)
The research Objective was to identify the types of households that exist in the Saoka sub-district in Maladum mes district at 4 RT and countermeasures. The method used is descriptive method, what is meant by qualitative here is looking for meaning, understanding, and understanding of a phenomenon, events, as well as human life by being directly and/or indirectly involved in a researched, contextual, and comprehensive setting. Based on the results of research conducted in sud-district Saoka at 4 RT, garbage the most are types of inorganic waste, plastic waste, bottle waste, and garbage. The way to handle waste that is done is by: (1) recycling and (2) burning.